1987
DOI: 10.1111/j.1432-1033.1987.tb10913.x
|View full text |Cite
|
Sign up to set email alerts
|

Somatic antigens of Pseudomonas aeruginosa. The structure of O-specific polysaccharide chains of the lipopolysaccharides from P. aeruginosa O5 (Lanyi) and immunotype 6 (Fisher)

Abstract: Lipolysaccharides were isolated from dry bacterial cells of Pseudomonas aeruginosa OSa,b,c, OSa,b,d, 05a,d (Lanyi classification) and immunotype 6 (Fisher classification) by the Westphal procedure. Their polysaccharide chains were built up of trisaccharide repeating units containing ~-xylose, 2-acetamido-2,6-dideoxy-~-galactose and a new sialic acid-like sugar, the di-N-acyl derivative of 5,7-diarnino-3,5,7,9-tetradeoxy-~-glycero-~-mannononulosonic (pseudaminic) acid. Formyl, acetyl and (R)-3-hydroxybutyryl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
46
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(56 citation statements)
references
References 34 publications
10
46
0
Order By: Relevance
“…The relatively small difference in proton chemical shifts for H3ax and H3eq (⌬␦ H 0.59 ppm) indicated that I had the ␣ configuration with the C1 carboxyl group occupying the equatorial position. In ␤-Pse, the difference for H3ax and H3eq tends to be larger and ranges from ⌬␦ H 0.77 to 1.10 ppm (29,32,34). The chemical shift for C6 at ␦ C 71.9 ppm also supported that C1 occupies the equatorial position since when C1 is axial, C6 typically resonates downfield at ␦ C 74.2 ppm (34).…”
Section: Cmp-5-acetamido-7-acetamidino-3579-tetradeoxy-l-glycero-␣mentioning
confidence: 86%
See 1 more Smart Citation
“…The relatively small difference in proton chemical shifts for H3ax and H3eq (⌬␦ H 0.59 ppm) indicated that I had the ␣ configuration with the C1 carboxyl group occupying the equatorial position. In ␤-Pse, the difference for H3ax and H3eq tends to be larger and ranges from ⌬␦ H 0.77 to 1.10 ppm (29,32,34). The chemical shift for C6 at ␦ C 71.9 ppm also supported that C1 occupies the equatorial position since when C1 is axial, C6 typically resonates downfield at ␦ C 74.2 ppm (34).…”
Section: Cmp-5-acetamido-7-acetamidino-3579-tetradeoxy-l-glycero-␣mentioning
confidence: 86%
“…By comparing chemical shifts and coupling constants to those reported for Pse in the literature, the absolute configuration of CMPPse5NAc7Am (I) was determined to be L-glycero-L-manno (14,29,30,(32)(33)(34). The relatively small difference in proton chemical shifts for H3ax and H3eq (⌬␦ H 0.59 ppm) indicated that I had the ␣ configuration with the C1 carboxyl group occupying the equatorial position.…”
Section: Cmp-5-acetamido-7-acetamidino-3579-tetradeoxy-l-glycero-␣mentioning
confidence: 99%
“…The difference between chemical shifts of the signals for H3,, and H3,, in the 'H-NMR spectrum of PS, , , and PSNaOAc, Bt3N amounts to 0.84-1 .OO ppm, being characteristic [7,8,10, 111 for the axial orientation of carboxyl group in glycosides of neuraminic acid and related sugars (a difference less than 0.6ppm was reported [12] for glycosides of 5,7-diamino-3,5,7,9-tetradeoxy-~-glycero-~-manno-nonulosonic (pseudaminic) acid with the equatorial carboxyl…”
Section: Resultsmentioning
confidence: 99%
“…The threo configuration of the fragment C7-8 followed from the "C chemical shift 19.4 ppm of the signal for C9 in the 13C-NMR spectrum of PSNaOAc, Et3N (according to the published data [7,11,12,14,151 this resonance lies at 19.6-20.3 ppm in the isomer with the threo configuration and at 16.2-17.7 pprn in that with the erythro configuration). The configuration of the side chain of the higher sugar was confirmed independently by the NOE observed on H6 at 4.25 ppm as a result of pre-irradiation of H9 at 1.27 ppm.…”
Section: Resultsmentioning
confidence: 99%
“…The sugar residues are attached via a glycosidic linkage to the OH group of the 3-hydroxybutyramido substituent ; monomers are thus linked via both glycosidic and amidic linkages. Different pseudaminic acid derivatives have been described previously as components of the polysaccharides isolated from Pseudomonas aeruginosa, Shigella boydii and Vibrio cholerae [6][7][8][9][10][11] but this is the first report of the completely determined structure of a pseudaminic acid-containing homopolysaccharide in a rhizobial bacterium. Although different homopolysaccharides composed of a higher sugar of this class have been reported [12][13][14][15], and a polysaccharide with this class of glycosidic linkage has been described [9], this is the first report of a homopolymer of pseudaminic acid derivative with this type of glycosidic linkage.…”
Section: Introductionmentioning
confidence: 99%